Drying characteristics of biological porous media during convective drying - Huilin, Wang; Tao, Lu; Quanguo, Zhang (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Experiments with potatoes were carried out in order to analyze the variation of the temperature and the mean dry basis moisture content over time, the effect of the drying conditions on the drying rate, and the relationship between deformation and dry basis moisture content. A two-way sequentially coupled thermo-hydro-mechanical math model was developed on the basis of Fickian diffusion theory, Fourier’s law of heat conduction and thermoelasticity mechanics in order to analyze the spatio-temporal distributions of moisture, temperature and drying stresses in the potatoes. The transient mathematical model, composed of a system of partial differential equations, was solved by finite difference methods. The numerical results obtained by using the mathematical model were in good agreement with the experimental data. The variations in temperature and moisture distributions, drying curves and stresses within potatoes over time were simulated, and the ways in which these are affected by the drying conditions were discussed. This work could help in developing an understanding of the relationship between mass and heat transfer, shrinkage, stress, and physical degradation of biological materials. Keywords: heat and mass transfer, deformable porous media, THM coupling, mathematical modeling DOI: 10.3965/j.ijabe.20160905.2057 Citation: Wang H L, Lu T, Zhang Q G. Drying characteristics of biological porous media during convective drying. Int J Agric & Biol Eng, 2016; 9(5): 194－207.